Autophagy in neurodegeneration: New insights underpinning therapy for neurological diseases. Issue 4 (16th April 2020) - Corti, Olga; Blomgren, Klas; Poletti, Angelo; Beart, Philip M.
Abstract: In autophagy long‐lived proteins, protein aggregates or damaged organelles are engulfed by vesicles called autophagosomes prior to lysosomal degradation. Autophagy dysfunction is a hallmark of several neurodegenerative diseases in which misfolded proteins or dysfunctional mitochondria accumulate. Excessive autophagy can also exacerbate brain injury under certain conditions. In this review, we provide specific examples to illustrate the critical role played by autophagy in pathological conditions affecting the brain and discuss potential therapeutic implications. We show how a singular type of autophagy‐dependent cell death termed autosis has attracted attention as a promising target for improving outcomes in perinatal asphyxia and hypoxic‐ischaemic injury to the immature brain. We provide evidence that autophagy inhibition may be protective against radiotherapy‐induced damage to the young brain. We describe a specialized form of macroautophagy of therapeutic relevance for motoneuron and neuromuscular diseases, known as chaperone‐assisted selective autophagy, in which heat shock protein B8 is used to deliver aberrant proteins to autophagosomes. We summarize studies pinpointing mitophagy mediated by the serine/threonine kinase PINK1 and the ubiquitin–protein ligase Parkin as a mechanism potentially relevant to Parkinson's disease, despite debate over the physiological conditions in which it is activated in organisms. Finally, with the example of the autophagy‐inducing agent rilmenidine and its discrepant effects in cell culture and mouse models of motor neuron disorders, we illustrate the importance of considering aspects such a disease stage and aggressiveness, type of insult and load of damaged or toxic cellular components, when choosing the appropriate drug, timepoint and duration of treatment. Abstract : Autophagy is a process whereby damaged or abnormal components, such as proteins or organelles, are degraded in the cell. In this manuscript, we use specific examples to illustrate how alterations in this process are involved in various pathological conditions of the brain, reviewing selected mechanisms associated with its detrimental enhancement or impairment. Further, we provide prospects for therapy and discuss key issues to be considered when exploring therapeutic avenues based on the manipulation of autophagy.